The Implementation of Salam-Contract For Agriculture Financing Through Islamic-Corporate Social Responsibility (Case Study of Paddy Farmers in Tuban Regency Indonesia) - Ahmad Hudaifah; Bambang Tutuko; Sawarjuwono Tjiptohadi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
This research is aimed at discovering a stable financial schemingformula or model that would be compatible with the natural characteristics ofa paddy farming cycle in Tuban. The qualitative research employs the use of anactive participatory community through the means of a focus group discussion, anin-depth interview and face to face interviews with respective stakeholders andkey informants. The Salam contract, which is highly beneficial is a prospectivefinancial scheme that terminates the long business chain found in most businessesin Indonesia. The Corporate Social Responsibility which is managed through theSyariah approach (I-CSR) from a company, can become the solution to bridgethe gap found in the implementation of funds for a Salam contract. The Salamcontract applicability is dependent on the Islamic farmer cooperatives (BMT), aunit of joint venture organization serving as the key players in the execution ofthe function of a paddy warehouse-trading agent and direct financing to farmers.Strong support also comes from the zakat, infāq, and shodaqoh institution (LAZ)whose role is educating and encouraging the paddy farmers’ skills and competency,especially to enable them access end-user markets using the aid of informationtechnology. Penelitian ini betujuan untu menemukan formula skema pembiayaanpertanian yang stabil sesuai dengan karakteristik alamiah pertanian padidi Kabupaten Tuban. Metode penelitian kualitatif dipergunakan dalammenyelesaikan penelitian ini dengan partisipasi aktif komunitas melaluimedia diskusi kelompok, wawancara mendalam tatap muka dan observasikepada informan kunci dan pihak yang terlibat secara langsung dalam tata-niaga pertanian padi di Kabupaten Tuban. Kontrak salam adalah skemapembiayaan yang sangat menguntungkan bagi petani dan pada aplikasinyamampu mengambil peran pembiayaan distributor dalam tata niaga pertanianpadi. Islamic Corporate Social Responsibility (I-CSR) yang dikelola berdasarkanprinsip ekonomi Syariah dari perusahan yang beroperasi di wilayah Tuban bisamenjadi solusi dana yang dikembangkan untuk pembiayaan pertanian yangdihindari oleh perbankan karena siklus bisnis yang berbeda. Keberlangsungan kontrak salam pertanian untuk komoditas padi akan bergantung pada koperasipetani yang terdiri dari koperasi simpan pinjam Syariah (BMT), gudang padi,penggilingan padi dan unit perdagangan yang kesemuanya disebut sebagai KUB(Kelompok Usaha Bersama). Dukungan yang kuat juga berasal dari Lembagazakat, infāq dan shodaqoh, yang memiliki peran untuk melakukan pelatihankeahlian petani dan membantu memenuhi kebutuhan dasar petani yang menjadianggota dalam KUB.